READING COMPREHENSION ANALYSIS OF 5TH GRADE STUDENTS AT SD NEGERI TANGKISAN, PURWOREJO REGENCY - Darojah, Zakya; Widiyono, Yuli; Nurhidayati, Nurhidayati (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research aimed to assess the reading comprehension skills of 5th-grade students at SD Negeri Tangkisan and to identify the factors that affect these abilities. Using a descriptive, qualitative method with a case study approach, this research sample consists of 16 5th-grade students from the 2024/2025 academic year. Data collection included observation, interviews, and tests. Analysis followed the Miles and Huberman model, which involves data collection, reduction, display, and drawing conclusions or verification, with validity ensured through technique and source triangulation. The findings revealed that students' reading comprehension was at a moderate level. Specifically, students achieved a 70.31% score in literal comprehension, indicating their ability to understand facts and details in the text. For interpretive comprehension, students scored 63.75%, suggesting some difficulty in extracting implied meanings. Critical comprehension was 65.62%, indicating a moderate ability to evaluate and analyze texts. These results indicate that while students generally grasp reading material, they still require guidance, particularly in inferencing and analysis. Influencing factors were categorized as external (including text characteristics, environmental reading habits, availability of reading materials, and supporting facilities) and internal (such as initial reading skills, interest and attitude, memory capacity, and emotional state during reading). The overall results indicate a moderate comprehension level among 5th-grade students at SD Negeri Tangkisan, highlighting the need for more effective learning strategies and reading practices to enhance students’ critical and interpretive skills.